Visualizing the active paths in morphologically defective organic thin-film transistors - Zhang, Wen-Shan; Matthiesen, Maik; Günther, Benjamin; Wensorra, Jakob; Fischer, Daniel; Gade, Lutz H.; Zaumseil, Jana; Schröder, Rasmus R. (Advanced electronic materials, 2021)
The charge-carrier mobility of organic semiconductors extracted from thin-film transistors is highly dependent on film morphology. Morphological defects can lead to the underestimation of charge transport properties, which may impede the rational design of novel materials. Herein, a novel analytical method is presented to functionally characterize entire active layers of solution-processed thin-film transistors. By correlating imaging and spectroscopy of secondary electrons, nano-sized morphological defects are discovered and the effective current paths between source and drain electrodes are directly visualized. After image-processing, the as-measured mobility values of zone-cast thin-films of a tetraazaperopyrene derivative are corrected, obtaining charge-carrier mobilities of up to five times higher than the as-measured values. The direct visualization of the electric functionality of the organic thin-films facilitates a unique quantification of the impact of morphological defects and provides a solid benchmark to estimate the potential for further improvement of device performance.